2011
DOI: 10.1080/00797308.2011.11800833
|View full text |Cite
|
Sign up to set email alerts
|

Coherence, Competence, and Confusion in Narratives of Middle Childhood

Abstract: Middle childhood is a pivotal time in character development during which enduring internal structures are formed. Fiction can offer insights into the cognitive and affective shifts of this developmental phase and how they are transformed in adulthood. While the success of beloved books for latency age children lies in the solutions they offer to the conflict between the pull toward independence and the pull back to the safety of childhood, the enduring stories for adults about children in their middle years ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Because of the easiness to obtain the activation energy ( E a ) and pre-exponential factor (σ 0 ), the Arrhenius equation is also widely used to express ionic conductivity for amorphous conduction. For the case of fast ionic conductors, the relation between σ 0 and E a in the Arrhenius equation can be described by the semi-empirical Meyer-Neldel (MN) rule [49]: logσ0=sans-serifαEa+sans-serifβ=EakTD+lnKω0 where T D is a characteristic temperature, k is the concentration term and ω 0 is the ion attempt frequency (hopping rate between adjacent adsorption sites [50,51]) related to σ 0 [23]. The Meyer-Neldel (MN) rule is also applicable for mixed-phase (inhomogeneous polymer and additive that are not in a common solvent) and blend-based (homogeneous solution of two components in a common solvent) polymer electrolytes [52,53].…”
Section: Ion Transport In Binary and Composite Polymer Electrolytesmentioning
confidence: 99%
“…Because of the easiness to obtain the activation energy ( E a ) and pre-exponential factor (σ 0 ), the Arrhenius equation is also widely used to express ionic conductivity for amorphous conduction. For the case of fast ionic conductors, the relation between σ 0 and E a in the Arrhenius equation can be described by the semi-empirical Meyer-Neldel (MN) rule [49]: logσ0=sans-serifαEa+sans-serifβ=EakTD+lnKω0 where T D is a characteristic temperature, k is the concentration term and ω 0 is the ion attempt frequency (hopping rate between adjacent adsorption sites [50,51]) related to σ 0 [23]. The Meyer-Neldel (MN) rule is also applicable for mixed-phase (inhomogeneous polymer and additive that are not in a common solvent) and blend-based (homogeneous solution of two components in a common solvent) polymer electrolytes [52,53].…”
Section: Ion Transport In Binary and Composite Polymer Electrolytesmentioning
confidence: 99%
“…While the younger children's mourning was tinged with anger and resignation, the preadolescents' mourning had a sad resignation accompanied by hope for a better, independent future. The importance of successful mourning in middle childhood development has also been found by Shustorovich and Weinstein (2011).…”
Section: R E S U Lt S F R O M C O N T E M P O R a Ry P S Yc H Oa N A Ly T I C L At E N C Y R E S E A R C Hmentioning
confidence: 90%
“…While we chose to explicate a single story, similar themes of separation, ambivalence toward the parental figures and awareness of mortality and sexuality, can also be found in stories by such disparate authors as James Joyce, Grace Paley, Isaac Babel and Eudora Welty 2 . Elsewhere (Weinstein and Shustorovich, 2010, in press) we have suggested that these stories help readers work through the enduring conflicts of latency. Some clarify the experience of childhood by importing adult knowledge and perspective into its narrative, while others offer readers a chance to make a coherent whole out of their fragmented memories by describing the unconscious disorganizing aspects of this period.…”
Section: Introductionmentioning
confidence: 99%